Self‐Driven Photodetectors: GaSe/MoS2 Heterostructure with Ohmic‐Contact Electrodes for Fast, Broadband Photoresponse, and Self‐Driven Photodetectors (Adv. Mater. Interfaces 9/2020). Issue 9 (7th May 2020) - He, Zhenbei; Guo, Junxiong; Li, Shangdong; Lei, Zhicheng; Lin, Lin; Ke, Yizhen; Jie, Wenjing; Gong, Tianxun; Lin, Yuan; Cheng, Tiedong; Huang, Wen; Zhang, Xiaosheng
Abstract : In article number 1901848 Zhenbei He, Wen Huang, Xiaosheng Zhang and co‐workers demonstrate a vertically aligned GaSe/MoS2 heterostructure with Ohmic‐contact indium tin oxide (ITO) electrodes. Transparent glass is used as a substrate for the device. Therefore, glass is used as background in the cover picture. The self‐driven GaSe/MoS2 heterojunction photodetector can realize light detection without external power. Therefore, the ITO/GaSe/MoS2 /ITO device looks like a battery. In addition, compared with GaSe/MoS2 heterostructure with Schottky‐contact Ni/Au electrodes, the GaSe/MoS2 heterostructure with Ohmic‐contact ITO electrodes demonstrates more outstanding performance.